MEDIA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Winarko, Winarko; Mulyono, Edi; Patimah , Siti; Afifatun, Siti; Sajdah , Smeilisa (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
Islamic Religious Education (PAI) learning media are tools or learning resources used to facilitate the learning process in understanding Islamic values ??and teachings. PAI learning media aims to help students gain a comprehensive and contextual understanding of PAI content. The development of Islamic Religious Education learning media includes various approaches, including printed media (books, modules), audiovisual media (educational videos), and digital platforms (applications, e-learning) that are adapted to the needs and characteristics of students. By utilizing digital technology, Islamic Religious Education learning media seeks to involve students actively and critically in understanding Islam, fostering noble morals, and instilling Islamic values. This research aims to improve understanding, interest, and application of Islamic religious values ??in students. Through qualitative methods in research on Islamic Religious Education (PAI) learning media, it is possible to gain an in-depth understanding of the effectiveness, experiences, and perceptions of students and teachers in the PAI learning process using various media. Qualitative methods allow researchers to explore how learning media, whether technology-based, visual, or traditional, influence students' interest, understanding, and engagement in religious studies. The results of the research achieved several significant results, both in terms of understanding the material, student involvement, and internalization of religious values ??in everyday life. The expected results from the use of effective Islamic Religious Education learning media are: Increasing Understanding of Material, Increasing Interest and Motivation to Learn, Developing Critical and Reflective Thinking Skills, Internalizing Religious Values ??and Increasing Student Involvement and Participation